Orthostatic hypotension and symptomatic subclinical orthostatic hypotension increase risk of cognitive impairment: an integrated evidence review and analysis of a large older adult hypertensive cohort. (24th July 2018) - Peters, Ruth; Anstey, Kaarin J; Booth, Andrew; Beckett, Nigel; Warwick, Jane; Antikainen, Riitta; Rockwood, Kenneth; Peters, Jean; Bulpitt, Christopher J
Abstract: Aims: Systematically reviewing the literature found orthostatic hypotension (OH) to be associated with an increased risk of incident dementia but limited data were available in those at highest risk, the hypertensive oldest-old. Our aim was to analyse the relationship between OH and incident cognitive decline or dementia in this group and to synthesize the evidence base overall. Method and results: Participants aged ≥80 years, with hypertension, were from the Hypertension in the Very Elderly Trial (HYVET) cohort. Orthostatic hypotension was defined as a fall of ≥15 mmHg in systolic and or ≥7 mmHg in diastolic pressure after 2 min standing from a sitting position. Subclinical orthostatic hypotension with symptoms (SOH) was defined as a fall <OH but with unsteadiness, light-headedness, or faintness in the week before blood pressure measurement. Proportional hazard regression was used to examine the relationship between baseline OH, SOH, and cognitive outcomes. There were 3121 in the analytical sample, 538 with OH. Orthostatic hypotension was associated with increased risk of cognitive decline (906 events), hazard ratio (HR) 1.36 (95% confidence interval 1.14–1.59). For incident dementia (241 events), HR 1.34 (0.98–1.84). When competing risk of cardiovascular events were taken into account results were HR 1.39 (1.19–1.62) and HR 1.34 (1.05–1.73), respectively. Subclinical orthostatic hypotension was associated with an increased risk of cognitive decline HR 1.56 (1.12–2.17) and dementia HR 1.79 (1.00–3.20). Combining the results from the HYVET cohort in a meta-analysis with the existing published literature in this area found a 21% (9–35%) increased risk of dementia with OH. Conclusion: Orthostatic hypotension indicates an increased risk of dementia and cognitive decline. SOH may also be considered a risk factor, at least in older hypertensive adults. Questions remain regarding the mechanisms and whether interventions to reduce impact of OH could protect cognition.